Blacklight blue - May, Peter, 1951- (May, Peter, 1951- Enzo files, 2008)
Beginning an investigation into a third cold case described in a book by Parisian journalist Roger Raffin, Scottish scholar and amateur detective Enzo MacLeod finds himself confronting a diagnosis of a terminal illness and attacks by someone out to frame him for murder.